Educational Puzzle Strategies for Managing Hyperactive Children and Enhancing Learning Concentration: A Qualitative Study - Astrid Wulandari; Syarifuddin Syarifuddin; Yayuk Kusumawati (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
This study aims to analyze how puzzle-based learning activities can support teachers in directing the excessive energy of hyperactive children into more focused learning tasks. This research employed a qualitative descriptive approach. Data were collected through classroom observations, interviews with teachers, and documentation of learning activities involving students who exhibit hyperactive tendencies. The results show that educational puzzles provide structured and engaging stimulation that encourages children to focus on problem-solving tasks. Through puzzle activities, students gradually develop patience, self-control, and sustained attention during classroom learning. In addition, the strategy helps teachers create a more conducive learning environment by channeling students’ active behavior into meaningful activities. These findings indicate that educational puzzle strategies contribute positively to improving students’ learning concentration and participation in the classroom. Therefore, teachers are encouraged to integrate puzzle-based activities as an alternative strategy to support the management of hyperactive behavior in early childhood learning settings.